(3HjYI CejQ GdeDefjf ehdGfG SdjeGfs - (3CHh GdQHjY SdjeGf Hf eMeO Hf YHO Gddg Hf ESeGYjd GdTQja GdYdhj, Gdehdj SdjeGf,J (B1238 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fXe HGdNdGaI Ted GdOjf hGdOfjG, hCYdi bOQgG Ydi cd bOQ acGfJ dgG GdOQLI GdYdjG s
(3BNQgG (B:s
(3fUQg Gddg hfUQ Hg hCHbi GdNdGaI aj HjJg Edi jhe GdJfGO hUdi Gddg Ydi SjOfG eMeO NGJe GdfHjjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B172 - (3U(B187s
(3hgPg GdHjYI hQOJ aj GdESJbUG dC NHGQ Ohd GdeZQH GdCbUi (B87/8s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B133s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B70 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B487) s
Keywords: (3GdJGQjNs